Characterisation of negative social impact risks within pre-deployment carbon dioxide utilisation projects - Newman, Alex J. K.; Rothman, Rachael H.; Styring, Peter (Frontiers in Energy Research, 2024)
As the youngest of the three sub-fields within sustainability assessment, development of social impact assessment lags behind life cycle and techno-economic assessments. This is manifested in comparatively lacking methodological maturity. The calculation of impact indicator results, achieved through the use of characterisation models, is a prime example of the field's immaturity. This research initially identifies current methodologies observed within social impact assessment. This reveals that impact pathway characterisation models, analogous to those seen in life cycle assessment, have primarily been neglected; instead, research has been focused on less reproducible and more subjective reference scale approaches. Redressing this balance, a set of seven UNEP and SETAC indicators are evaluated, developing novel impact pathway-based characterisation models. Focussing on the effects of stimulating and de-stimulating factors on indicators, identifying hotspots where negative social impacts are likely to arise. The presented methodologies are tailored to applications involving the assessment of potential carbon dioxide utilisation (CDU) value chains. This focus results in open access characterisation models that are indiscriminate of technology readiness level, requiring no primary process data. Data from the World Bank and its partner organisations are utilised, generating complete results across all indicators for 129 countries. Development of these quantifiable characterisation models delivers significant value in the standardisation of assessment procedure and facilitates inter-assessment comparability, a benefit to stakeholders ranging from practitioners to commissioners.